DETEKSI INDIKASI FRAUD DENGAN TEKNOLOGI AUDIT - Fitri Annisa; Lutfi Harris (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2011)
The aim of this research is describing how to detect fraud using Computer Assisted Audit Technique (TABK).This research focus on purchasing fraud. Qualitative research method has used in this research.Symptoms offraud can be separated into six categories: accounting anomalies, internal control weaknesses, analyticalanomalies, extravagant lifestyle, unusual behavior, and tips and complaint. Auditor can use TABK especially todetect accounting anomalies, and analytical anomalies. The using TABK in detecting fraud can increase theeffectiveness and efficiency of audit process. In the company which was implementing computer basedinformation system, most of the data was stored in digital format, it could not read directly, and only a littlephysical audit tracking. Therefore, this is the chance for the auditor to use TABK to detect symptoms of fraud.When the auditor find fraud’s symptoms, he or she must investigate whether the symptoms resulted from actualfraud or by other factors. The result of the test using TABK is just a mediator for the auditor to find fraud’ssymptoms. So, the auditors have to do further investigation. By using TABK, the process to detect fraud will beable to be done more effective and efficient.